Synthesis and Molecular Structure of 99Tc Corroles. Issue 52 (23rd November 2016) - Einrem, Rune F.; Braband, Henrik; Fox, Thomas; Vazquez‐Lima, Hugo; Alberto, Roger; Ghosh, Abhik
Abstract: The first 99 Tc corroles have been synthesized and fully characterized. A single‐crystal X‐ray structure of a 99 TcO triarylcorrole revealed nearly identical geometry parameters as the corresponding ReO structure. A significant spectral shift between the Soret maxima of TcO (410–413 nm) and ReO (438–441 nm) corroles was observed and, based on two‐component spin–orbit ZORA TDDFT calculations, ascribed to relativistic effects in the Re case. The syntheses reported herein potentially pave the way toward 99m Tc‐porphyrinoid‐based radiopharmaceuticals. Abstract : In a key step toward corrole‐based radiopharmaceuticals, the first 99 Tc corroles have been synthesized, including one that has been fully characterized by single‐crystal X‐ray structure analysis.